High avidity antigen-specific CTL identified by CD8-independent tetramer staining. - Choi, E; Chen, J; Wooldridge, L; Salio, M; Lissina, A; Lissin, N; Hermans, I; Silk, J; Mirza, F; Palmowski, M; Dunbar, P; Jakobsen, B; et al. (2003)
Tetrameric MHC/peptide complexes are important tools for enumerating, phenotyping, and rapidly cloning Ag-specific T cells. It remains however unclear whether they can reliably distinguish between high and low avidity T cell clones. In this report, tetramers with mutated CD8 binding site selectively stain higher avidity human and murine CTL capable of recognizing physiological levels of Ag. Furthermore, we demonstrate that CD8 binding significantly enhances the avidity as well as the stability of interactions between CTL and cognate tetramers. The use of CD8-null tetramers to identify high avidity CTL provides a tool to compare vaccination strategies for their ability to enhance the frequency of high avidity CTL. Using this technique, we show that DNA priming and vaccinia boosting of HHD A2 transgenic mice fail to selectively expand large numbers of high avidity NY-ESO-1(157-165)-specific CTL, possibly due to the large amounts of antigenic peptide delivered by the vaccinia virus. Furthermore, development of a protocol for rapid identification of high avidity human and murine T cells using tetramers with impaired CD8 binding provides an opportunity not only to monitor expansion of high avidity T cell responses ex vivo, but also to sort high avidity CTL clones for adoptive T cell transfer therapy.